Environment of deposition of the sandstones of Lower Vindhyans of parts of Durg district, Madhya Pradesh, India - Chandra, M.; Singhal, B. B. S.; Awasthi, A. K. (Journal of Nepal Geological Society, 1996)
Present paper attempts to establish the environment of deposition of the sandstones belonging to the Chandarpur Group exposed in parts of the Durg district, Madhya Pradesh (India). Grain size and shape analyses of the sandstones are carried out. Vertical variations of the different grain size statistics of the fluvial and beach sediments are also studied. A multivariate linear discriminant technique was adopted for discriminating the sediments of these two environments. The palaeocurrents are towards north, northeast and southeast. Petrographic studies and provenance analysis of the sandstones show that the beach environment is richer in quartz and poorer in matrix as compared to the fluvial ones. The sandstones have been clearly differentiated with the help of multivariate discriminant analysis using thin section modal constituents like quartz, feldspars, iron oxide, matrix, etc. Results of the lithostratigraphic, grain size and petrographic studies fairly tally with each other suggesting that the sandstones under study were deposited under two very different fluvial and beach environments.